Measuring Migration Status Based on the Place of Marriage Overestimates the Share of Male Migrants in Historical Populations. Evidence From Dutch Marriage Certificates - Matthias Rosenbaum-Feldbrügge; Paul Puschmann (Historical Life Course Studies)
Thanks to the construction of large databases such as LINKS and GENLIAS based on Dutch civil certificates, our knowledge of individual demographic behavior in the past has improved significantly. However, the use of such research infrastructures also introduces some potential pitfalls, as these databases do not contain all information available from the original sources. For instance, variables that are available on the original source but lacking in LINKS are the places of residence of the bride and the groom at marriage. A common practice among researchers using LINKS and GENLIAS is therefore to identify migrants by comparing an individual’s birth place with the place of marriage. The place of marriage, however, is not necessarily identical to the place of residence, because couples traditionally contracted their marriage in the bride's or bride's parents' municipality of residence. It is therefore particularly likely that grooms are erroneously considered as migrants even though they had never moved before marriage. In this paper we explore whether this poses a problem to studies using the place of marriage as an equivalent to the place of residence. This will be achieved with the help of the marriage certificates release from the Historical Sample of the Netherlands (HSN), which, unlike LINKS, contains both the place of marriage of the couple and the residence of the bride and groom, and allows us to compare the findings derived from both approaches. The analyses show that identifying migrants based on place of marriage causes indeed a significant overestimation of male migrants, but not of female migrants. We therefore suggest the use of a couple's place of first childbirth as a robustness check to avoid overestimating male migration in the past.